Evaluasi Program Provider Initiated Testing And Counseling (PITC) Pada Ibu Hamil Pada Masa Pandemi Covid-19 Di Puskesmas Muara Badak - Sari, Anita; Pakki, Irfansyah Baharuddin; Asrianti, Tanti (Wal'afiat Hospital Journal, 2022)
Provider Initiated Testing and Counseling (PITC) is an important strategy to increase coverage of HIV testing for pregnant women as well as efforts to control HIV/AIDS in Indonesia and is part of the Maternal and Child Health (KIA) program. During the COVID-19 pandemic, new HIV/AIDS infections tended to increase, especially among housewives. During the COVID-19 pandemic, the Muara Badak Health Center found new HIV cases and tended to increase, while HIV screening for pregnant women decreased. This study aims to determine the implementation of the Provider Initiated Testing and Counseling (PITC) program for pregnant women during the COVID-19 pandemic at the Muara Badak Health Center in terms of process (assessment of the mechanism for implementing the PITC program for pregnant women) and output (factors related to pregnancy). with program success). This type of research is cross sectional and the sampling technique used is accidental sampling. Collecting data using questionnaires and observation sheets with a sample of 86 pregnant women, Bivariate analysis using the Fisher's Exact Test and the Kolmogorov-Smirnov Test with a 95% confidence level (α = 0.05). The results showed that the implementation of the Provider Initiated Testing and Counseling (PITC) program evaluation activities for pregnant women during the COVID-19 pandemic at the Muara Badak Health Center in terms of process, was declared to have gone quite well with a score of 32 (63%), while the implementation of evaluation activities the PITC program for pregnant women during the COVID-19 pandemic at the Muara Badak Health Center in terms of output stated, the results of statistical tests between the success of the PITC program and the basic principles of PITC (p=1,000), knowledge (p=1,000), attitudes (p=0.000) using the Kolmogorov-Smirnov Test, and resistance (p=1,000). In conclusion, there is no relationship between the success of the PITC program and the basic principles of PITC, knowledge, and barriers. There is a relationship between the success of the PITC program and attitude. Muara Badak Health Center is expected to be able to monitor and evaluate the implementation of PITC.